2015
DOI: 10.1007/s00520-015-2858-7
|View full text |Cite
|
Sign up to set email alerts
|

Inadequate pain management in cancer patients attending an outpatient palliative radiotherapy clinic

Abstract: The rate of undertreatment is similar to that reported in past studies; however, the rates have shown a slight increase in our palliative radiotherapy clinic since the last assessment. Inadequate management of cancer pain continues to be a problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 25 publications
1
32
0
Order By: Relevance
“…A study in South Africa by Beck and Falkson 21 reported that only 21% of patients with cancer had achieved 100% pain relief. A Canadian study by Vuong et al 22 reported that 33.3% of patients reported inadequate pain management, and 106 of 354 patients reported severe pain despite taking strong opioids. In India, however, the proportion of inadequately managed pain was 79%, as reported by Saxena et al 23 …”
Section: Discussionmentioning
confidence: 99%
“…A study in South Africa by Beck and Falkson 21 reported that only 21% of patients with cancer had achieved 100% pain relief. A Canadian study by Vuong et al 22 reported that 33.3% of patients reported inadequate pain management, and 106 of 354 patients reported severe pain despite taking strong opioids. In India, however, the proportion of inadequately managed pain was 79%, as reported by Saxena et al 23 …”
Section: Discussionmentioning
confidence: 99%
“…Radiation oncologists often treat patients with palliative radiotherapy for painful metastatic and advanced cancers, and patients' pain must be well controlled if they are to tolerate their radiation treatments and optimize quality of life until palliative radiation reaches its full efficacy, a process that can take 2 to 3 weeks. 19 Studies have shown that patients referred for palliative radiotherapy for symptomatic bone metastases are often not taking analgesics or are receiving weak opioids or non-opioids, 20,21 thus making opioid management a critical skill set for radiation oncologists. This skill set is necessarily one that allows flexibility in prescribing between alternative routes and potencies to achieve analgesia across a broad range of clinical scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the improvement recorded in pain management after using this strategy, evidence indicates that patients living with cancer still experience high levels of pain in situations where it is possible to reduce their suffering . It has been reported that around 25–33% of patients living with cancer are receiving insufficient pain management . In addition, two systematic reviews that assessed the quality of pain management in adult patients with cancer revealed modest improvements in pain management, but stated that one‐third of patients who experience pain continue to be under‐treated …”
Section: Introductionmentioning
confidence: 99%